2021
DOI: 10.3390/infrastructures6050068
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Benefits of the Shinkansen Network

Abstract: High speed rail (HSR) networks have been an essential catalyst in stimulating and balancing regional economic growth that ultimately benefits the society as a whole. Previous studies have revealed that HSR services sustainably yield superior social values for people, especially for adults and those of working age. This has become an advantage of HSR networks over other forms of public transportation. The Shinkansen network in Japan is one of most successful HSR models. Its services bring significant social adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The LCA reflects the amounts of energy consumption and CO2 emissions at each stage of the life cycle. Some researchers have pointed out that LCA analysis results can lead to reductions in the long-term effects on humans and wildlife, improvement in the quality of products, and decreased amounts of GHG emission (Patra, 2007;Banar and Ozdemir, 2015;Rungskunroch et al, 2021aRungskunroch et al, , 2021bRungskunroch et al, , 2021c. As shown in Figure 3, the life cycle of a HSR network contains four stages: (i) the manufacturing, pre-assembly and logistics stage of where LCE = life cycle of energy consumption; LCCO2 = life cycle of CO2 emissions; ECi = total energy consumption (GJ) in stage i; CEi = total CO2 emission (t) in stage i; i = {manufacturing and pre-assembly, operation, maintenance, demolition}.…”
Section: Lca For Hsr Networkmentioning
confidence: 99%
“…The LCA reflects the amounts of energy consumption and CO2 emissions at each stage of the life cycle. Some researchers have pointed out that LCA analysis results can lead to reductions in the long-term effects on humans and wildlife, improvement in the quality of products, and decreased amounts of GHG emission (Patra, 2007;Banar and Ozdemir, 2015;Rungskunroch et al, 2021aRungskunroch et al, , 2021bRungskunroch et al, , 2021c. As shown in Figure 3, the life cycle of a HSR network contains four stages: (i) the manufacturing, pre-assembly and logistics stage of where LCE = life cycle of energy consumption; LCCO2 = life cycle of CO2 emissions; ECi = total energy consumption (GJ) in stage i; CEi = total CO2 emission (t) in stage i; i = {manufacturing and pre-assembly, operation, maintenance, demolition}.…”
Section: Lca For Hsr Networkmentioning
confidence: 99%
“…Rail transportation is often introduced as an alternative to road transportation because of its socio-economic benefits. Numerous studies have identified innumerable socioeconomic benefits associated with rail transportation, including increased accessibility, connectivity, agglomeration, land use change, job creation, increased property value, increased retail activity, reduced commute time, reduced congestion, and security [11,12,7,13,14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research confirms previous research by Chen and Vickerman, [7], which found that rail stations had a favorable socioeconomic impact on residents living near them, as well as a positive net present value. Jack Rungskunruch and Kaeumruen [14] did a study on the socioeconomic benefits of Japan's Shinkansen network, utilizing Pearson's Correlation (PCC) to ascertain the railway impact on individuals of all genders and ages. The study examined the broad impact of social factors on population dynamics, education, age dependency, job chances, and death rate, utilizing a unique dataset covering 55 years of social factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is difficult to apply to other networks. Rungskunroc h et al[64] ✓ The research pointed out the benefit of the land price after the coming of HSR.…”
mentioning
confidence: 99%